Mechanomyography for studying force fluctuations and muscle fatigue - Shinohara, M.; Sogaard, K. (Exercise and Sport Sciences Reviews, 2006)
Measurement of the transverse displacement of the skin over a contracting muscle is known as the surface mechanomyogram. With the concurrent measurement of the electromyogram and twitch force, the mechanomyogram can provide supplementary information about muscle activity and motor performance during such tasks as fatiguing contractions and attempts to perform steady contractions.